Updates on the epidemiology of age-related macular degeneration - Jonas, Jost B.; Panda-Jonas, Songhomitra (Asia-Pacific journal of ophthalmology, 2017)
This meta-analysis reports on current estimates of the prevalence of age-related macular degeneration (AMD) based on a review of recent meta-analyses and literature research. Within an age of 45-85 years, global prevalences of any AMD, early AMD, and late AMD were 8.7% [95% credible interval (CrI), 4.3‒17.4], 8.0% (95% CrI, 4.0‒15.5), and 0.4% (95% CrI, 0.2-0.8). Early AMD was more common in individuals of European ancestry (11.2%) than in Asians (6.8%), whereas prevalence of late AMD did not differ significantly. AMD of any type was less common in individuals of African ancestry. The number of individuals with AMD was estimated to be 196 million (95% CrI, 140‒261) in 2020 and 288 million (95% CrI, 205‒399) in 2040. The worldwide number of persons blind (presenting visual acuity < 3/60) or with moderate to severe vision impairment (MSVI; presenting visual acuity < 6/18 to 3/60 inclusive) due to macular disease in 2010 was 2.1 million [95% uncertainty interval (UI), 1.9‒2.7] individuals out of 32.4 million individuals blind and 6.0 million (95% UI, 5.2‒8.1) persons out of 191 million people with MSVI. Age-standardized prevalence of macular diseases as cause of blindness in adults aged 50+ years worldwide decreased from 0.2% (95% UI, 0.2‒0.2) in 1990 to 0.1% (95% UI, 0.1‒0.2) in 2010; as cause for MSVI, it remained mostly unchanged (1990: 0.4%; 95% UI, 0.3‒0.5; 2010: 0.4%; 95% UI, 0.4‒0.6), with no significant sex difference. In 2015, AMD was the fourth most common cause of blindness globally (in approximately 5.8% of blind individuals) and third most common cause for MSVI (3.9%). These data show the globally increasing importance of AMD.